Karakterisktik Kekerasan dalam Rumah Tangga terhadap Perempuan Ditinjau dari UU No. 23 Tahun 2004 - Herlyanti Yuliana Anggraeny Bawole; Grace Yurico Bawole; Yulianty Sanggelorang; Dingse Pandiangan Pandiangan (JPAI: Jurnal Perempuan dan Anak Indonesia, 2023)
This study aims to analyze and describe domestic violence against women in the perspective of criminal law. The research method used is normative legal research by studying laws, concepts and various approaches in conducting research. The legal materials used are laws and regulations, books, glossaries, encyclopedias. The results of the study show that the characteristics of domestic violence against women in terms of Law No. 23 of 2004 that violence that occurs in the household environment is limited and closed, even women as victims of violence are generally under the influence of perpetrators such as there is a fear of refusing what is his will. Law Number 23 of 2004 concerning the Elimination of Domestic Violence as a legal instrument that prevents and protects victims of domestic violence against women. Empowering women in various aspects must remain a priority. There must be concrete efforts to help victims of violence gain access to equal rights and norms, social and religious beliefs, as well as the applicable legal system. Women as victims of domestic violence often experience violence in the personal sphere, both in relation to being a wife or as another family member. Violence in the family sphere is violence that is considered as something that normally happens, even as part of education carried out by husbands on wives, internal problems that other people should not interfere with, even perpetrators or victims very often cover up the real incident from other people for different reasons. ABSTAK Penelitian ini bertujuan untuk menganalisis dan mendiskripsikan kekerasan dalam rumah tangga terhadap perempuan dalam prespektif hukum pidana. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan mengkaji undang-undang, konsep serta berbagai pendekatan dalam pelaksanaan penelitian. Bahan hukum yang digunakan adalah peraturan perundanga- undangan,buku- buku, glorosium, ensiklopedia. Hasil penelitian menunjukan bahwa karakteristik kekerasan dalam rumah tangga terhadap perempuan ditinjau dari UU No.23 Tahun 2004 bahwa kekerasan yang terjadi dalam lingkungan rumah tangga tempatnya terbatas dan tertutup, bahkan perempuan sebagai korban kekerasan pada umumnya berada di bawah pengaruh pelaku seperti ada rasa takut bila menolak apa yang menjadi kehendaknya. Undang- undang Nomor 23 tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga sebagai instrument hukum yang mencegah dan melindungi korban kekerasan dalam rumah tangga terhadap perempuan.